Supraclavicular Approach to Ultrasound-Guided Brachiocephalic Vein Cannulation in Children and Neonates - Merchaoui, Zied; Lausten-Thomsen, Ulrik; Pierre, Florence; Ben Laiba, Maher; Le Saché, Nolwenn; Tissieres, Pierre (Frontiers in Pediatrics, 2017)
The correct choice of intra vascular access in critically ill neonates should be individualized depending on the type and duration of therapy, gestational and chronological age, weight and/or size, diagnosis, clinical status, and venous system patency. Accordingly, there is an ongoing demand for optimization of catheterization. Recently, the use of ultrasound-guided cannulation of the subclavian vein (SCV) has been described in children and neonates. This article gives an overview of the current use of ultrasound for achieving central venous catheter placement in the SCV or the brachio-cephalic vein (BCV) in neonates. More than 1250 catheters have been reported inserted in children and neonates for a cumulated success rate of 98.4% and the complication rate is reported to be low. The technical aspects of various approaches are discussed and we offer our recommendation of an ultrasound-guided technique for SCV and BCV cannulation based on our experience in a large NICU setting. Although the cannulation the SCV or BCV does not substitute the use of peripherally inserted central catheters (PICC) or umbilical venous central catheters (UVCC) in neonates, it is a feasible route, even in very small children who are in need of a large caliber central venous access.